CLASSIFICATION OF THE SCIENTIFIC HERITAGE OF SHEIKH MUHAMMAD SADIK MUHAMMAD YUSUF (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the scientific heritage of Sheikh Muhammad Sadiq Muhammad Yusuf. His works are analyzed in the direction of creed, jurisprudence, hadith science, Quranic sciences, translation, and socio-educational direction. Within the framework of the article, the significance of Sheikh Muhammad Sadiq’s works and their comparative analysis with other works are also presented.
Keywords: Islam; Quran; Hadith; Fiqh; Aqidah; Science; Translation; Sufism; Ethics; Tafsir